# math

posted by .

find the functional values requested in the problem F(x)=x^2-25t
(a)F(5t)=
(b)F(6t)=

• math -

a)
if f(x) = x^2 - 25t
f(5t) = (5t)^2 - 25t = 25t^2 - 25t

so the second one in the same way.

Notice we had a function of x, that is, f(x)
so only the terms that contain x's are affected in the substitution, unless you have a typo.

## Similar Questions

1. ### MATH

Assume f(x) = x2 + 4. Find the functional value requested. f(-6) =
2. ### ALGEBRA

Find the functional values requested in the problem. h(x)=5 x-1
3. ### ALGEBRA

Assume f(x) = x2 + 3. Find the functional value requested. f(-7)
4. ### ALGEBRA

Assume f(x) = x2 + 3. Find the functional value requested. f(-7) =
5. ### ALGEBRA

Find the functional values requested in the problem. h(x)=3 x-1 (a) h(0) = (b) h(-7) =
6. ### ALGEBRA

Assume f(x) = x2 + 4. Find the functional value requested. f(-3) =
7. ### Math

Find the functional values requested in the problem; h(x)=5x-4 (a) h(0)= (b)h(-11)=
8. ### Math

How will I work this problem? Find the functional values requested in the problem. h(x)=3x-4 (a) h(0) = (b) h(-10)=
9. ### Math

Assume f(x) = x2 + 3. Find the functional value requested. f(-5) =
10. ### math

The particular solution of the differential equation dy/dt equals y over 4 for which y(0) = 20 is y = 20e−0.25t y = 19 + e0.25t y = 20 e0.25t - my answer y = 20e4t

More Similar Questions